“Adakah Harapan untuk Tulang-tulang Kering Ini?”: Sebuah Tafsir Sosio-Historis terhadap Yehezkiel 37:1-14 - Hendrik, Isakh; Mangililo, Ira D. (Institut Agama Kristen Negeri Toraja, 2023)
The crisis caused by the COVID-19 pandemic bring pain and suffering, and hope is the only thing that helps us deal with the impact of the pandemic. The issue of hope is also raised in the book of Ezekiel. The Babylonian conquest caused the Israelites to experience total social, economic, political, cultural, and religious destruction. Using a socio-historical approach, this article aims to analyze Ezekiel 37:1-14. The results of reading the text show that the prophecy about the resurrection of dry bones gives hope that there will be a resurrection of life and restoration for the Israelites, which is marked by their return to their land. Dry bones can also be used to describe our present condition when facing the COVID-19 pandemic. Even though Ezekiel's book has different historical conditions and backgrounds from our current context, the theological reflection on Ezekiel 37:1-14 gives hope for God's power and sovereignty, which can reverse crisis situations and restore and renew our current life.